PERTUMBUHAN DAN PRODUKSI RIMPANG TEMU LAWAK DI POLYBAG YANG BENIHNYA HASIL KULTUR IN VITRO - Hadipoentyanti, Endang; Syahid, Sitti Fatimah (Perhimpunan Biologi Indonesia, 2001)
ABSTRACTGrowth and Yield of Temoe Lawak in Polybag which Planting Material from In Vitro Culture. The growth and yield of temoe lawak (Curcuma xanthorrhiza Roxb.) from in vitro culture was conducted in the green house, Bogor from October 2000 to September 2001. The materials were obtained from temoe lawak plant two months after acclimatizating. The plant were planted in the polybag 60 cm x 60 cm. The treatments were consisted of the mixtures of soil and cattle manure with the proportional of 1 : 1 ; the soil and rice husk (1 : 1) ; the soil, cattle manure and rice husk (1 : 1 : 1). The experiment was designed according to randomized block design with three replicates and ten polybags per replicate .The parameters observed were plant performance, growth percentage at 5 and 10 months, rhizome weight per plant, length and width of primery rhizome, roots and water rhizome weight per plant. The result of experiment showed that the growth percentage of plant were 100% on ten months for all treatments. The growth and rhizome performance were similar with the parent. The best treatment for growth was the mixture of soil and cattle manure on the proportional of 1 : 1, with tiller numbers (3,57) , leaves number (18,2), plant height (140,6 cm) in five moths, rhizomes weight per plant (472,8 g), length and width of primery rhizome each 8,1 cm and 6,3 cm in ten months.Key words : Curcuma xanthorrhiza Roxb, growth, yield, in vitro